A Real Effort vs. Standard Public Goods Experiment: Overall More All-or-Nothing, Lower Average Contributions and Men Become More Selfish in the Effort-Loss Frame - Tobias Schütze; Philipp C. Wichardt; Philipp Christoph Wichardt (Center for Economic Studies and ifo Institute (CESifo), 2023)
Many environment related public goods require investment of time or effort rather than simply money. Yet, most experimental studies on public good games focus on a distribution of money. In the present paper, we report results from an experiment (N=181) comparing an effort based public goods game (both in gain/loss frame) to a standard (gain/loss) public goods game. We find lower average contributions and more free-riders in the effort treatments. These differences are highly significant statistically and in terms of effects size; the most notable effect showing for men in the loss frame (comparing standard vs. effort, contributions drop from 76.7% to 17.0%, free-riders increase from 8.3% to 82.6%, full-contributors drop from 50.0% to 13.0%). The findings suggest that the provision of environmental public goods faces more impediments than common experimental findings indicate. Moreover, they suggest that especially men become more self-focused when required to mitigate a loss with effort. Given that many environmental public goods are about avoiding losses by taking action and that most political decision makers are still men, the latter result seems to be relevant from a policy perspective.
Keywords: C91; D91; H41; Q54; 330; public goods; real effort; climate change; loss aversion; gender effects